Cultural topographies of the new Berlin - Bauer, Karin, 1958-; Hosek, Jennifer Ruth (Berghahn Books, 2018)
Since Unification and the end of the Cold War, Berlin has witnessed a series of uncommonly intense social, political, and cultural transformations. While positioning itself as a creative center populated by young and cosmopolitan global citizens, the "New Berlin" is at the same time a rich site of historical memory, defined inescapably by its past even as it articulates German and European hopes for the future. Cultural Topographies of the New Berlin presents a fascinating cross-section of life in Germany's largest city, revealing the complex ways in which globalization, ethnicity, economics, memory, and national identity inflect how its urban spaces are inhabited and depicted.